PLACE OF 'SAKET' IN HINDI-POETRY: हिंदी-काव्य में ‘साकेत’ का स्थान - Mineshwari (International Journal of Research -GRANTHAALAYAH, 2019)
Maithilisharan is such a seeker of Gupta Indian Manisha, who has been successful in connecting with the ancient Indian ideology and modern thought and way of life dedicated to the protection of humanity and culture. Saket was his successful attempt. It is a best-management poem that added an emotional tone to Indian beliefs and beliefs. The ancient content is presented in a new environment. The origins of the creation of 'Saket' were two inspirations - "(1) Rambhakti, (2) the desire to see and understand the Indian life in a holistic way." 1 Rambhakti naturally refers to Ramakavya, life-daring life- Towards poetry. मैथिलीषरण गुप्त भारतीय मनीशा के ऐसे साधक हैं, जो मानवता और संस्कृति के रक्षार्थ प्राणपन समर्पित रहे भारतीय प्राचीन विचारधारा व आधुनिक विचार और जीवन-पद्धति से जोड़ने में सफलता हासिल किए हैं। ‘साकेत’ इनका सफल प्रयास रहा। यह एक सर्वोत्तम प्रबंध-काव्य है, जो भारतीय आस्थाओं और मान्यताओं को भावनात्मक स्वर मिला। प्राचीन विशयवस्तु को नए परिवेष में प्रस्तुत किया है। ‘साकेत’ के सृजन के मूल दो प्रेरणाएँ थी- ‘‘(1) रामभक्ति, (2) भारतीय जीवन को समग्र रूप में देखने और समझने की लालसा।’’1 रामभक्ति स्वभावतः रामकाव्य की ओर संकेत करती है, जीवन-दर्षन जीवन-काव्य की ओर।